2020
DOI: 10.3390/su12031075
|View full text |Cite
|
Sign up to set email alerts
|

Operational Performance and Degradation Influenced Life Cycle Environmental–Economic Metrics of mc-Si, a-Si and HIT Photovoltaic Arrays in Hot Semi-arid Climates

Abstract: Life cycle metrics evolution specific to the climate zone of photovoltaic (PV) operation would give detailed insights on the environmental and economic performance. At present, vast literature is available on the PV life cycle metrics where only the output energies ignoring the degradation rate (DR) influence. In this study, the environ-economic analysis of three PV technologies, namely, multi-crystalline silicon (mc-Si), amorphous silicon (a-Si) and hetero-junction with an intrinsic thin layer (HIT) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Even though PV has many benefits, it has a few significant disadvantages because its output is zero at night and can vary considerably during the day, depending on weather conditions [64]. Hence, in the PV plants, especially in DSPV, an ESS is highly recommended that enhances the operating reliability by providing the continuous power supply even in the night time [13].…”
Section: Solar Photovoltaic Power Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though PV has many benefits, it has a few significant disadvantages because its output is zero at night and can vary considerably during the day, depending on weather conditions [64]. Hence, in the PV plants, especially in DSPV, an ESS is highly recommended that enhances the operating reliability by providing the continuous power supply even in the night time [13].…”
Section: Solar Photovoltaic Power Plantsmentioning
confidence: 99%
“…SPVPP's also possesses a few main challenges: grid integration, performance-related issues, and power quality issues [64][65][66]. In addition to these, financing and social acceptance are also hindering Overall, from Figure 4, it is understood that solar is widely accepted in many nations.…”
Section: Solar Photovoltaic Power Plantsmentioning
confidence: 99%
“…Likewise, Dag and Buker 60 have reported the lower degradation rate of HIT modules as compared with m‐Si module which is 0.1%/year. Rajput et al 61 have also reported the low degradation of HIT technology.…”
Section: Resultsmentioning
confidence: 95%
“…It was assumed that the PV had an efficiency of 15.37% [90] and a degradation rate of 0.7% each year, which is higher than the average degradation rate of 0.5% [91]. The degradation of the PV is included in the calculation because it can affect the electricity production by the PV during the life cycle, the life cycle cost, and the CO 2 emissions reduction potential, as discussed in [92]. HP E is the electricity used by the heat pumps, AUX E is the sum of the backup heater, and pump electricity demands.…”
Section: Energy and Life Cycle Cost (Lcc) Calculationsmentioning
confidence: 99%